System for activation of metals by cyclic stresses at thermographic inspection - Базалєєв, Микола Іванович; Бандурян, Борис Багдасарович; Брюховецький, Василь Володимирович; Клепіков, В'ячеслав Федорович; Литвиненко, Володимир Вікторович; Прохоренко, Євген Михайлович (Eastern-European Journal of Enterprise Technologies, 2013)
The active thermographic method of construction materials inspection - thermodynamic thermal imaging inspection, which uses the energy of cyclic stresses for activation of thermal processes on irregularities and defects of solid bodies and their thermal development in the field of infrared radiation, is proposed. The method is based on the features of transformation of elastic waves energy into the heat on defect structures of solids, which are developed in the form of temperature anomalies on the surface and are sufficient to identify them with modern thermal imaging systems. For practical implementation of the method of thermodynamic thermal imaging inspection of materials, a scheme of the system was proposed, which provides the activation of thermal fields in the environment of controlled facility by applying cyclic stresses to it. Thermographic information on the state of facility is registered by technical means of thermal imaging control. The possibility of identifying microstructural irregularities and defects (cracks, flaws, inclusions) in metals under cyclic stresses of samples, with the help of modern thermal imaging means of thermal development control, was experimentally confirmed. Herewith, defects of material microstructure during absorbing the energy of elastic waves created thermal anomalies, the amplitude of which exceeded the background temperature value by 0, 4°C or more.